(untitled) (Journal of the College of Basic Education, 2022)
The aim of this study is to know the most important factors and components of power of the Islamic Republic and the impact of these factors on Iraq. It worked to be the dominant state in the region. With its strengths and the most important of these is the geographical location. It is one of the countries of the Middle East, as it has a huge area of ​​(1,64,195) million square kilometers. And this extension has an impact on the diversity of the regions, climatic and vegetation, and the activity of the population and the economy. It also has a view of the most important water bodies. It has the longest coastline overlooking the Arabian Gulf, with a length of (635) nautical miles. The Iranian geopolitical strength point is its control of the Strait of Hormuz, which is one of the most important waterways in the world. In terms of population strength, the population of the Islamic Republic in the year 2020 reached (81) million people. 25% of them are under the age of (15) years, and this is something that represents a large future population base that has an effective impact on Iranian politics. The Islamic Republic was able to exploit the diverse ethnic composition to create a process of communication with other nationalities in neighboring countries. As for the other factor, it is the economic factor, and it is one of the most important factors in the strength of the state. The Islamic Republic is considered the second largest economy in the Middle East and North Africa. It is located on huge oil reserves. As well as coal - natural gas - iron ore and others.As for its military power. It has worked to develop its military capabilities. The GFP website was ranked in 2019. The Islamic Republic is among the 20 strongest countries in terms of military capabilities. This classification takes into account - the number and diversity of weapons - nuclear stockpiles - geographical factors - demographic strength - logistical flexibility - natural materials - possession of sea coasts - financial stability - political and military leadership. As for its electronic power. It has achieved clear qualitative advances in technological capabilities. This made it among the most powerful (5) countries electronically in the world. As for the ideological factor, it appears in the foreign policy of the Islamic Republic when it supports and agrees with its interests, objectives, policy and national orientations seeking to expand it regionally and globally. And take advantage of all the circumstances and possibilities.